The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1073/pnas.2216430120
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines and linear DNA mediate bacterial threat assessment of bacteriophage infection

Abstract: Monitoring the extracellular environment for danger signals is a critical aspect of cellular survival. However, the danger signals released by dying bacteria and the mechanisms bacteria use for threat assessment remain largely unexplored. Here , we show that lysis of Pseudomonas aeruginosa cells releases polyamines that are subsequently taken up by surviving cells via a mechanism that relies on Gac/Rsm signaling. While intracellular polyamines spike in surviving … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Incubation of purified enzymes with putrescine and acetyl-CoA further established PA1472 as the likely P. aeruginosa SpeG homolog ( Figure 2F and Figure S5A ). We next determined the kinetic properties of PA1472 toward putrescine and confirmed that like SpeG, it is most active at the high end of intracellular putrescine concentrations ( Km = 30.7 ± 9.9 mM) ( Figure 2G ) 41 . Consistent with PA1472 possessing putrescine N -acetyltransferase activity, its dimer AlphaFold2 predicted structure resembled the crystal structure of SpeG (3WR7, RMSD 1.891), despite the low % amino acid ID shared between the primary sequences ( Figure 2H ) 44 .…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Incubation of purified enzymes with putrescine and acetyl-CoA further established PA1472 as the likely P. aeruginosa SpeG homolog ( Figure 2F and Figure S5A ). We next determined the kinetic properties of PA1472 toward putrescine and confirmed that like SpeG, it is most active at the high end of intracellular putrescine concentrations ( Km = 30.7 ± 9.9 mM) ( Figure 2G ) 41 . Consistent with PA1472 possessing putrescine N -acetyltransferase activity, its dimer AlphaFold2 predicted structure resembled the crystal structure of SpeG (3WR7, RMSD 1.891), despite the low % amino acid ID shared between the primary sequences ( Figure 2H ) 44 .…”
Section: Resultsmentioning
confidence: 60%
“…To our knowledge, until this study there were no experimental data demonstrating SpeG's activity toward putrescine. This is striking, as putrescine is the most abundant polyamine in the bacterial pathogens investigated here, while spermidine is present at about 5-to-10-fold lower concentrations [38][39][40][41] . Notably, under physiologic conditions, intracellular spermidine concentrations (1-5 mM) can be an order of magnitude greater than the corresponding Khalf for SpeG (~600 µM), indicating that SpeG already operates on this substrate at or near its Vmax and perturbations in spermidine concentration are likely to have little impact on the rate of N-acetylspermidine production.…”
Section: Discussionmentioning
confidence: 94%
“…We found that norspermidine signaling through the MbaA receptor is necessary and sufficient for V. cholerae cells to collectively commit to the biofilm state in response to lysis, and that this commitment protects cells from phage infection and Type-VI secretion system killing. Previous studies of P. aeruginosa have demonstrated that exposure to polyamine danger signals present in lysate, in conjunction with the presence of linear DNA, limits phage replication 31 , 32 . It remains possible that a biofilm response also contributes to the P. aeruginosa protection mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it would enable the demand for nitrogen-rich compounds to be met from recycling the limited pools of nitrogenous organic matter available (Barker et al, 2013), for example through necromassassociated organic matter liberated during lysis from the prolific levels of viral predation typical of glacier surfaces (Bellas et al, 2013). Indeed, polyamines such as those detected here have recently been implicated as 'danger signals' following the lytic discharge of polyamine-enriched intracellular milieu consequent to viral infection (de Mattos et al, 2023). Metagenomic analyses of cyanobacterial mats in other Arctic habitats highlight the importance of nutrient scavenging and recycling as an economical strategy for growth in the challenging prevailing conditions (Varin et al, 2010).…”
Section: Metabolomes Reflect Nitrogen Assimilation and Recyclingmentioning
confidence: 93%